2011
DOI: 10.1007/s10384-011-0078-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiglaucoma drugs on the ocular surface in rabbits: a fixed-combination drug versus two concomitant drugs

Abstract: A fixed-combination antiglaucoma drug is beneficial in reducing adverse ocular surface changes in long-term use. This is believed to be due to the smaller concentration of preservatives contained in the fixed-combination drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, it is possible that the lack of differences found in our study was due to the fact that our patients presented with either none or only mild corneal disorders before being switched to TTFC therapy. Many of the patients with glaucoma use the same or more than two kinds of anti-glaucoma ophthalmic solutions [3], and Cho et al [23] reported that a fixed-combination anti-glaucoma ophthalmic solution is beneficial in reducing adverse ocular surface changes in long-term use. Consequently, TTFC may be a better choice for glaucoma treatment over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that the lack of differences found in our study was due to the fact that our patients presented with either none or only mild corneal disorders before being switched to TTFC therapy. Many of the patients with glaucoma use the same or more than two kinds of anti-glaucoma ophthalmic solutions [3], and Cho et al [23] reported that a fixed-combination anti-glaucoma ophthalmic solution is beneficial in reducing adverse ocular surface changes in long-term use. Consequently, TTFC may be a better choice for glaucoma treatment over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed combination was proven effective and well-tolerated in terms of symptoms, whereas improving the quality of life could also explain the increased treatment compliance [41,42]. In addition, experimental rabbit models highlight that the fixed combination medication with a lower concentration of preservatives reduces the ocular surface changes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [ 13 ] reported that a fixed-combination antiglaucoma ophthalmic solution was beneficial for reducing adverse ocular surface changes during long-term use. We previously compared ocular adverse effects between PGA monotherapy and travoprost-Tim fixed-combination therapy with the same protocol used in the present study, and we reported no significant difference in ocular adverse effects between the two groups [ 9 ].…”
Section: Discussionmentioning
confidence: 99%